Critical-sized bone defects regeneration using a bone-inspired 3D bilayer collagen membrane in combination with leukocyte and platelet-rich fibrin membrane (L-PRF): An in vivo study. (April 2020) - Fahimipour, Farahnaz; Bastami, Farshid; Khoshzaban, Ahad; Jahangir, Shahrbanoo; Eslaminejad, Mohamadreza Baghaban; Khayyatan, Fahimeh; Safiaghdam, Hannaneh; Sadooghi, Yeganeh; Safa, Majid; Jafarzadeh Kashi, Tahereh S.; Dashtimoghadam, Erfan; Tayebi, Lobat
Highlights: β-TCP-reinforced collagen scaffolds support cellular activity in vitro. In the conducted preclinical study, up to three-fourths of the defect is regenerated with lamellar bone when the scaffold is used in combination with L-PRF membrane. The designed scaffold can be further investigated for the drug and cell delivery for bone tissue regeneration. Abstract: Objectives: We aim to develop a 3D-bilayer collagen (COL) membrane reinforced with nano beta-tricalcium-phosphate (nβ-TCP) particles and to evaluate its bone regeneration in combination with leukocyte-platelet-rich fibrin (L-PRF) in vivo . Background data: L-PRF has exhibited promising results as a cell carrier in bone regeneration in a number of clinical studies, however there are some studies that did not confirm the positive results of L-PRF application. Methods: Mechanical & physiochemical characteristics of the COL/nβ-TCP membrane (1/2 & 1/4) were tested. Proliferation and osteogenic differentiation of seeded cells on bilayer collagen/nβ-TCP thick membrane was examined. Then, critical-sized calvarial defects in 8 white New Zealand rabbits were filled with either Col, Col/nβ-TCP, Col/nβ-TCP combined with L-PRF membrane, or left empty. New bone formation (NBF) was measured histomorphometrically 4 & 8 weeks postoperatively. Results: Compressive modulus increases while porosity decreases with higher β-TCP concentrations. Mechanical properties improve, with 89 % porosity (pore size ∼100 μm) in the bilayer-collagen/nβ-TCP membrane. The bilayer design also enhances the proliferation and ALP activity. In vivo study shows no significant difference among test groups at 4 weeks, but Col/nβ-TCP + L-PRF demonstrates more NBF compared to others (P < 0.05) after 8 weeks. Conclusion: The bilayer-collagen/nβ-TCP thick membrane shows promising physiochemical in vitro results and significant NBF, as ¾ of the defect is filled with lamellar bone when combined with L-PRF membrane.